PENGGUNAAN STRATEGI GRADASI WARNA DALAM MENINGKATKAN KREATIVITAS ANAK DI TAMAN KANAK KANAK - Erisna; Nurhafizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creativity is crucial for early childhood. However, many kindergarten children still struggle to express their ideas. This study aims to enhance children's creativity through a color gradation strategy. The method used was Classroom Action Research (CAR) in two cycles. The subjects were children in Group B at Jihad Kindergarten. Data were collected through observations of coloring activities and documentation of children's work. Before the action, children's creativity was at 20%. After the action, the percentage of children completing the coloring activity increased to 40%. Because it had not yet reached the minimum completion percentage, it was continued to Cycle II. In Cycle II, children's completion increased significantly, reaching 80%. In conclusion, the color gradation strategy has proven effective in significantly increasing the creativity of kindergarten children. Keywords: Color Gradation Strategy, Children's Creativity, Kindergarten.